PENGARUH BEBAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA RUMAH MAKAN KHAS BETAWI BABEH SADELI DI KOTA TANGERANG - Anthi Fathia Rida; Dira Karlina (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of workload and work discipline on employee performance at the Betawi Babeh Sadeli Typical Restaurant in Tangerang, both partially and simultaneously. This research method uses quantitative methods with a sample size of 60 respondents, the data analysis techniques used are: validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, simple linear regression test, multiple linear regression test, simple correlation coefficient test, multiple correlation coefficient test, coefficient of determination analysis test, t test and f test. Based on the results of the t test, it is obtained that the t count is 7,947 > 2.002 and the significance value for the workload variable (X1) is 0.000, the significant value is smaller than the probability value of 0.05 or 0.001 <0.05, meaning that the workload variable (X1) has a positive and significant effect on the employee performance variable (Y). at Rumah Makan Khas Betawi Babeh Sadeli Tangerang. Based on the results of the t test, the t value is 6,987 > 2.002 and the significance value for the work discipline variable (X2) is 0.000, the significant value is smaller than the probability value of 0.05 or 0.000 <0.05, meaning that the work discipline variable (X2) has a positive and significant effect on the employee performance variable (Y). at Rumah Makan Khas Betawi Babeh Sadeli Tangerang. Based on the results of the f test, the calculated f value is 53,731 > 2,770 and a significance value of 0.000 <0.05. So it can be concluded that the workload variable (X1) and work discipline (X2) simultaneously have a positive and significant influence on employee performance (Y). at Rumah Makan Khas Betawi Babeh Sadeli Tangerang.